Essential oil of Citrus hystrix DC.: A mini-review on chemical composition, extraction method, bioactivities, and potential applications in food and pharmaceuticals - Do Minh Long; Le Pham Tan Quoc (Plant Science Today, 2023)
Citrus hystrix DC. is a common herb in tropical regions. Its essential oils are now widely researched and applied because of their high economic value and safety for humans and are interesting materials for future trends. This review provides an extensive overview of the biological activities of C. hystrix essential oil, characterized predominantly by citronellal, ?-Pinene, sabinene, limonene, and terpinene-4-ol, which are deciding factors in antimicrobial, antioxidant, insect repellent, anti-tumor, and anti-inflammatory properties. Therefore, it is applied in the fields of food preservation and pharmaceuticals. However, these applications should consider the ratio of these components in the essential oil, which is variable when using materials from different parts of the plant and depending on the original location of the plant, growth stages, traditional or modern extraction methods, and pre-treatment methods.